2003
DOI: 10.3168/jds.s0022-0302(03)73801-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propylene Glycol or Fat Drench on Plasma Metabolites, Liver Composition, and Production of Dairy Cows During the Periparturient Period

Abstract: Forty-eight Holstein cows were used to determine the effects of short-term oral drenches of propylene glycol (PG) and Ca-soaps of palm oil fatty acids (fat) on plasma concentrations of key metabolites, liver composition, and milk production during the first 3 wk of lactation. Treatments (2 x 2 factorial arrangement) given orally once daily for the first 3 d postpartum were water (control), 500 ml of PG, 454 g of fat, or 500 ml of PG plus 454 g of fat. All treatments were administered as a total volume of 1.9 L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
56
3
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 22 publications
16
56
3
7
Order By: Relevance
“…In earlier studies (Waldo and Schultz, 1960;Studer et al, 1993;Grummer et al, 1994;Christensen et al, 1997), when blood were serially sampled for at least 1.5 h after PG administration, blood glucose and insulin concentrations were increased by PG. In contrast, PG did not affect blood glucose and insulin in other earlier studies (Sauer et al, 1973;Pickett et al, 2003) and the current study in which blood was sampled only once daily. Therefore, frequent sampling immediately after PG administration is necessary to monitor the effects of PG on blood insulin and glucose concentrations.…”
Section: Discussioncontrasting
confidence: 87%
“…In earlier studies (Waldo and Schultz, 1960;Studer et al, 1993;Grummer et al, 1994;Christensen et al, 1997), when blood were serially sampled for at least 1.5 h after PG administration, blood glucose and insulin concentrations were increased by PG. In contrast, PG did not affect blood glucose and insulin in other earlier studies (Sauer et al, 1973;Pickett et al, 2003) and the current study in which blood was sampled only once daily. Therefore, frequent sampling immediately after PG administration is necessary to monitor the effects of PG on blood insulin and glucose concentrations.…”
Section: Discussioncontrasting
confidence: 87%
“…These values are similar to those obtained in other studies (Gaál and Husvéth, 1983;Magdus et al, 1985) in the peripartal period in lactating cows and ewes. Contrary to the higher lipid content, the glycogen concentration showed lower levels (13.7-36.5 g/kg) in the peripartal period, which is also consistent with the results of other researchers (Pickett et al, 2003). The changes found in the hepatic lipid and glycogen contents reflect that the cows were in an energy-deficient condition.…”
Section: Discussionsupporting
confidence: 82%
“…Burhans et al (1997) reported no effect of PG on plasma NEFA and BHBA concentrations prior to parturition, whereas after parturition, PG drenches resulted in significantly decreased concentrations of NEFA and BHBA in plasma. Butler et al (2006) reported the improved energy balance and milk lactose content of cows drenched daily with either 500 ml of water or PG from day 10 before parturition until day 25 postpartum, but this effect was not observed in other studies (Pickett et al, 2003;Moallem et al, 2007). Those inconsistencies may be due to differences in quantity, timeframe and method of delivery of PG.…”
Section: Discussionmentioning
confidence: 85%